INTEGRASI NILAI-NILAI MODERASI DAN TOLERANSI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Putra, Fahmi Mandala; Fauzi, Muhamad (FIKRAH, 2024)
This article discusses the integration of moderation and tolerance values in Islamic Religious Education (PAI) as an effort to shape students’ moderate and tolerant character in society. Through a comprehensive study approach, this research explores teaching methods such as contextual, collaborative, value-based learning, as well as dialogue and simulation methods. The analysis results indicate that integrating these values strengthens mutual respect and appreciation for differences, while preventing extremism and intolerance. By instilling principles of balance and respect for diversity, Islamic religious education contributes to creating social harmony and noble character.